Pengelolaan Pertanian oleh Petani Berpendidikan Tinggi di Nagari Kampung Batu Dalam Tahun 2005-2024 - Sari, Septia Wulan; Fitrisia, Azmi (Jurnal Kronologi, 2025)
Agriculture, which plays a central role in food security and dominates the employment market for the Indonesian population, is predominantly limited to elementary school graduates. Interestingly, residents of Nagari Kampung Batu Dalam who have attained higher education continue to participate in agriculture. The purpose of this article is to examine how farmers with higher education manage their farms. This research uses a historical research method consisting of heuristic, critical, interpretive, and historiographic stages. Following the eruption of Mount Talang in 2005, the primary commodity shifted from passion fruit to vegetables. This transition period encouraged farmers' children to continue their education to higher education as a form of preparation for the post-disaster future. From 2005–2015, management varied depending on the type of vegetable crop, while from 2016–2024, management focused more on shallots. This adjustment is evident in how they cultivate the land, provide seeds, maintain the plants, and manage the harvest according to needs and changes occurring over time. The results of this study indicate that agricultural management by highly educated farmers reflects the continuity of agrarian traditions, with the ability to adapt to change, thus maintaining their relevant contribution to the socio-economic life of the local community. This study confirms that education does not change their identity as farmers, but rather enriches the way they practice agricultural traditions inherited from previous generations.